Meningkatkan Kerapian Menulis Dengan Media Buku Bergaris Tiga Pada Anak Tunagrahita Ringan (Single Subject Research Kelas IX-C SLB Perwari Padang) - azzahra, Hafiza; Armaini, Armaini (Jurnal Penelitian Pendidikan Khusus, 2022)
The difficulty in writing neatness faced by one of the IX graders who has mild mental retardation is the background of this research. Services are needed to improve the neatness of children's writing. The purpose of this study is to use a three-line book as a medium to help children's writing become more presentable. With the A-B-A design, this study uses the Single Subject Research (SSR) methodology. This study was conducted for 14 sessions, with the baseline condition (A1) (the child's initial condition) receiving 4 meetings, the intervention condition (B) receiving 6 meetings, and the baseline condition (A2) (the final condition condition) receiving 4 meetings. An approach to collecting data that involves testing and documentation. The research findings at baseline (A1) were 46.67%, 46.67%, 46.67%, and 46.67%. Meetings on intervention (B) were 80%, 86.67%, 93%, 86.67%, 86.67%, and 93%. At baseline (A2) the percentages of assessment were 86.67%, 80%, 73.33%, and 73.33%. Based on the results of the research, the media of three-lined books can improve the neatness of writing for children with mild mental retardation in grade IX.